2016
DOI: 10.1590/1519-6984.01915
|View full text |Cite
|
Sign up to set email alerts
|

Modeling habitat suitability of the invasive clam Corbicula fluminea in a Neotropical shallow lagoon, southern Brazil

Abstract: This study aimed to model the habitat suitability for an invasive clam Corbicula fluminea in a coastal shallow lagoon in the southern Neotropical region (-30.22, -50.55). The lagoon (19km 2 , maximum deep 2.5m) was sampled with an Ekman dredge in an orthogonal matrix comprising 84 points. At each sampling point, were obtained environmental descriptors as depth, organic matter content (OMC), average granulometry (Avgran), and the percentage of sand (Pcsand). Prediction performance of Generalized Linear Models (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
1
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 30 publications
1
6
1
3
Order By: Relevance
“…However, our model was able to be predictive due to the high number of samples. The precision of the predictive model using GLM was low when there were many 0 data in the study of Silveira and others [8]. After performing analysis with the data from three seasons in this model, it was shown that environmental factors affecting the habitation of the C. japonica by season were different.…”
Section: Discussionmentioning
confidence: 92%
“…However, our model was able to be predictive due to the high number of samples. The precision of the predictive model using GLM was low when there were many 0 data in the study of Silveira and others [8]. After performing analysis with the data from three seasons in this model, it was shown that environmental factors affecting the habitation of the C. japonica by season were different.…”
Section: Discussionmentioning
confidence: 92%
“…The continuous expansion of the distribution of C. fluminea in Brazilian water bodies, calls attention to the need for studies on population dynamics, modeling of habitat adequacy, as well as genetic variability of populations. These researches must be considered for the development of strategies to avoid the advance of new environments as well as to mitigate possible damages to the native fauna (Pigneur et al 2013;Silveira et al 2016;Fernandes et al 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Considering the high invasive potential of C. fluminea and its consequent economic and ecological impacts, it is important to understand the patterns of dispersion in non-native areas, accessing its updated distribution. This can help in predicting potential sites for new invasions and supporting preventive and controlling strategies, as well as identifying the main routes of introduction (Karatayev et al 2007;Ilarri and Sousa 2012;Silveira et al 2016). The objective of this study is to gather information on the current distribution of this species in Brazil and to record the occurrence of the species in the state of Piauí.…”
Section: Introductionmentioning
confidence: 99%
“…In this study we performed analysis based on four environmental parameters and the 6 relationships between two factors. Some studies used the GLM models and predicted the habitation of each species [15]- [18]. Each model used many environmental factors from 8 to 10.…”
Section: Discussionmentioning
confidence: 99%